Transcreating BMT4me: A protocol for adapting an mobile health medication adherence app for Spanish-speaking caregivers in pediatric hematopoietic stem cell transplant - Ashley Benhayoun; Mark Wang; Melissa Beauchemin; Emre Sezgin; Micah A. Skeens (Digital Health)
Objective Hematopoietic stem cell transplant is a life-saving procedure that treats patients with various conditions by transplanting hematopoietic stem cells from bone marrow. Mobile health apps could be useful in closing the digital divide and improving health equity among Spanish-speaking caregivers of children who undergo pediatric hematopoietic stem cell transplant. This study aims to transcreate the BMT4me adherence app originally designed for English-speaking caregivers for Spanish-speaking caregivers and evaluate the feasibility and usability. Methods This study consists of two phases. Phase 1 transcreates the existing BMT4me app for Spanish-speaking populations. App feedback is collected from three community advisory board focus groups ( n  = 10; each meeting will include the same 10 community advisory board members). Groups consist of members connected to the local Spanish-speaking population and participating in the Community Engagement Program at The Ohio State University Center for Clinical and Translation Science. Phase 2 tests the feasibility and usability of the Spanish BMT4me app with child–caregiver dyads ( n  = 30; 15 at site 1, n  = 15 at site 2) whose primary language is Spanish. This phase is mixed methods and incorporates both a qualitative approach (caregiver interviews) and quantitative measures (system usability scale). It is expected that app users in phase 2 will report above average system usability scale scores (>68%). It is also expected that >75% of families approached in phase 2 will enroll and complete the surveys in our study. Conclusion This protocol paper details the transcreation process of the BMT4me app into a Spanish version. The findings of the study will demonstrate the level of acceptability of the Spanish BMT4me app with participants whose primary language is Spanish. As a digital health intervention for an underrepresented population that is increasingly online yet historically underserved, this app can overcome health barriers and disparities and improve overall health equity.